APLIKASI ONLINE MENGGUNAKAN BASIS DATA FUZZY UNTUK MENENTUKAN KESESUAIAN LAHAN PERTANIAN - Wilis Kaswidjanti (Telematika, 2012)
One of the key factors in creating equitable development or development areasappropriate and one of them is the result of agricultural factors. Meanwhile, to determine thefeasibility of a farm or agricultural crops can be done by conducting an assessment of thefeasibility or suitability of an area with plants that can grow or live in the area. The method usedin the design of this software is the waterfall method. The software is built using PHPprogramming language, while using a MySQL database. The system accepts input in the formof plant data and data regions. While the output of the system in the form recommand crops andagricultural areas suitable for a particular area of life. With this software it will be more easier forusers to monitor and obtain information about both the area and the type of agricultural crops.Keywords: Fuzzy Database, Waterfall, Agriculture